Effect of annealing temperature on structural and magnetic properties of Co2TiO4 ceramics prepared by sol-gel method. Issue 6 (15th April 2019) - Fu, Q.S.; Li, C.L.; Meng, B.; Chakrabarti, C.; Zhang, R.; Chen, X.H.; Li, Y.H.; Yuan, S.L.
Abstract: In this paper, polycrystalline Co2 TiO4 ceramics have been synthesized using a sol-gel process followed by annealing at different temperatures. The lattice size and the average grain size of the samples increases with rise in annealing temperature. The temperature-dependent inverse paramagnetic susceptibilities recorded under zero-field-cooling condition have been fitted according to the Néel's expression for ferrimagnets. Subsequently, the molecular field constants and the corresponding exchange constants have been calculated. The fitting result shows that the magnetic interaction in the system becomes weaker as the annealing temperature rises. In addition, negative magnetization is observed during field-cooling process. The higher annealing temperature is beneficial to the growth of tetrahedral sublattice, leading to a decrease on compensation temperature. Furthermore, magnetization hysteresis loops for all the samples demonstrate the crucial role of grain size on the magnetic properties.